2021
DOI: 10.1002/jcsm.12713
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular adipose tissue in the quadriceps is more strongly related to recovery of activities of daily living than muscle mass in older inpatients

Abstract: Background The relationship between intramuscular adipose tissue at admission and recovery of activities of daily living (ADL) remains unclear. This study aimed to examine the relationship between intramuscular adipose tissue in the quadriceps at admission and recovery of ADL in older inpatients. Methods This prospective study included 404 inpatients aged ≥65 years (54.7% female). Recovery of ADL during hospital stay was assessed using the Barthel Index (BI) score at discharge, BI score change, and BI efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 39 publications
(192 reference statements)
0
36
1
Order By: Relevance
“…Based on a cross-sectional study with 371 older inpatients, Akazawa et al (11) reported that increased IntraMAT of the quadriceps was more strongly associated with declines in ADL than the loss of muscle mass. Most recently, the same team conducted a prospective cohort study with 404 older inpatients, and they found that increased IntraMAT of the quadriceps at admission was more strongly associated with worse recovery of ADL than the loss of muscle mass (10). Notably, both studies used ultrasound to measure muscle thickness and measured echo intensity as the surrogates of muscle mass and IntraMAT, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a cross-sectional study with 371 older inpatients, Akazawa et al (11) reported that increased IntraMAT of the quadriceps was more strongly associated with declines in ADL than the loss of muscle mass. Most recently, the same team conducted a prospective cohort study with 404 older inpatients, and they found that increased IntraMAT of the quadriceps at admission was more strongly associated with worse recovery of ADL than the loss of muscle mass (10). Notably, both studies used ultrasound to measure muscle thickness and measured echo intensity as the surrogates of muscle mass and IntraMAT, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the European Working Group of Sarcopenia in Older People2 (EWGSOP2) [ 4 ] suggested the importance of assessing not only muscle mass but also muscle quality, which includes the infiltration of fat into muscle, ratio of muscle strength to appendicular skeletal muscle mass, and bioimpedance analysis-derived phase angle, in the diagnosis of sarcopenia. Among the muscle quality parameters, intramuscular adipose tissue has been shown to be more closely related to muscle strength [ 5 , 6 ], stand-up, sit-down [ 5 , 7 ], and gait abilities [ 6 , 8 , 9 ], activities of daily living [ 10 , 11 ], swallowing function [ 12 , 13 ], onset of hip fracture [ 14 ], and mortality [ 15 ] than to muscle mass. Fraction of intramuscular adipose tissue is assessed with the echo intensity of the ultrasound image [ 5 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Only two previous studies addressed the associations of muscle mass and muscle quality with ADL in older inpatients (10,11). Based on a cross-sectional study with 371 older inpatients, Akazawa et al (11) reported that increased IntraMAT of the quadriceps was more strongly associated with declines in ADL than the loss of muscle mass.…”
Section: Discussionmentioning
confidence: 99%